Les frontières méditerranéennes de l’islam - Bernard Vincent (Les Cahiers de Framespa)
The Christians of Allah is the first of the four books written by Bartolomé Bennassar in collaboration with his wife Lucile. Based on an impressive inquisitorial documentation, this work, which combines the biographies of six characters with a quantitative study of 1550 Christian captives in Islamic territories, demonstrates the historic approach used by the authors. From an unprecedented perspective, it offers an analysis of the multiple aspects of the Christian-Islam relationship in the predominantly Mediterranean context of the 16th and 17th centuries. This book, which immediately became a hit, is also a classic thanks to the exceptional quality of its writing style.